Cardiac Migration of Endogenous Mesenchymal Stromal Cells in Patients with Inflammatory Cardiomyopathy - Caroline Schmidt-Lucke; Felicitas Escher; Sophie Van Linthout; Uwe Kühl; Kapka Miteva; Jochen Ringe; Thomas Zobel; Heinz-Peter Schultheiss; Carsten Tschöpe (Mediators of Inflammation)
Introduction. Mesenchymal stromal cells (MSC) have immunomodulatory features. The aim of this study was to investigate the migration and homing potential of endogenous circulating MSC in virus negative inflammatory cardiomyopathy (CMi). Methods. In 29 patients with n=23 or without n=6 CMi undergoing endomyocardial biopsies (EMB), transcardiac gradients (TCGs) of circulating MSC were measured by flow cytometry from blood simultaneously sampled from aorta and coronary sinus. The presence of MSC in EMB, cardiac inflammation, and SDF-1α mRNA expression were detected via immunohistochemistry and real-time PCR. Results. MSC defined as CD45−CD34−CD11b−CD73+CD90+ cells accounted for 0.010 [0.0025–0.048]%/peripheral mononuclear cell (PMNC) and as CD45−CD34−CD11b−CD73+CD105+ cells for 0.019 [0.0026–0.067]%/PMNC, both with similar counts in patients with or without cardiac inflammation. There was a 29.9% P<0.01 transcardiac reduction of circulating MSC in patients with CMi, correlating with the extent of cardiac inflammation (P<0.05, multivariate analysis). A strong correlation was found between the TCG of circulating MSC and numbers of MSC (CD45−CD34−CD90+CD105+) in EMB (r=-0.73, P<0.005). SDF-1α was the strongest predictor for increased MSC in EMB (P<0.005, multivariate analysis). Conclusions. Endogenous MSC continuously migrate to the heart in patients with CMi triggered by cardiac inflammation.